PENINGKATAN HASIL BELAJAR MENGGUNAKAN MODEL COOPERATIVE LEARNING TIPE MAKE A MATCH PADA PENDIDIKAN PANCASILA DI KELAS V SD NEGERI 20 PIAI KOTA PADANG - Wadina, Rahma; Waldi, Atri; Ningsih, Yarisda; Anita, Yesi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study was motivated by the low learning outcomes of students in Pancasila Education subjects in Class V of SD Negeri 20 Piai Padang City which can be seen from the average score that has not reached the Learning Objective Achievement Criteria (KKTP). The conventional learning model is less effective in increasing students' involvement and understanding in the learning process. The purpose of this study was to determine the effectiveness of the Cooperative Learning Type Make a Match learning model in improving student learning outcomes in Pancasila Education subjects. This study used the Classroom Action Research (PTK) method which was carried out in two cycles, with 28 students as research subjects. Data were collected through learning outcome tests, student observations and learning activity assessment questionnaires.The results showed a significant increase in student learning outcomes. The average score of students before the application of the Cooperative Learning Type Make a Match model was 69.67 then increased to 76.96 in cycle I and 87.86 in cycle II. In addition, students' activities during the learning process also increased with the percentage of students' involvement reaching 98.87% in cycle II. The data results show that students are more active and motivated in learning using this model. Based on this, it can be concluded that the application of the Cooperative Learning Type Make a Match model is effective in improving student learning outcomes in Pancasila education subjects in class V of SD Negeri 20 Piai Kota Padang. This study recommends that teachers consider using this learning model to improve the quality of learning in the classroom